1995
DOI: 10.1126/science.7716549
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Uninfected Lymphocytes by HIV-1 Tat Protein

Abstract: Infection by human immunodeficiency virus-type 1 (HIV-1) is typified by the progressive depletion of CD4 T lymphocytes and deterioration of immune function in most patients. A central unresolved issue in acquired immunodeficiency syndrome (AIDS) pathogenesis is the mechanism underlying this T cell depletion. HIV-1 Tat protein was shown to induce cell death by apoptosis in a T cell line and in cultured peripheral blood mononuclear cells from uninfected donors. This Tat-induced apoptosis was inhibitable by growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
356
2
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(373 citation statements)
references
References 37 publications
12
356
2
3
Order By: Relevance
“…Our findings also indicate that the Nef protein, present in small amounts in the HIV1 particles 45 and reported to either induce or repress cell death, [46][47][48][49] is not required for the killing of noncycling CD4 þ T cells in our model. Tat, another HIV1 protein that has been found to either induce 21,56,57 or repress 58 cell death in vitro, is not present in the viral particles, but is released by HIV1-producing cells. 59 Therefore, it is possible that Tat was present in the 100-450 nm fractions purified from supernatants of living, HIV1-transfected HeLa cells that we used as a source of virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also indicate that the Nef protein, present in small amounts in the HIV1 particles 45 and reported to either induce or repress cell death, [46][47][48][49] is not required for the killing of noncycling CD4 þ T cells in our model. Tat, another HIV1 protein that has been found to either induce 21,56,57 or repress 58 cell death in vitro, is not present in the viral particles, but is released by HIV1-producing cells. 59 Therefore, it is possible that Tat was present in the 100-450 nm fractions purified from supernatants of living, HIV1-transfected HeLa cells that we used as a source of virus.…”
Section: Discussionmentioning
confidence: 99%
“…The 39-40 kDa band corresponds to the described MW of the unprocessed, microvesicle-bound form of CD95L. 52,56 (d) Purified unstimulated primary CD4 þ T cells (10 6 /ml) were incubated with viruses (500 ng p24/ml) purified from living HeLa cells transfected with NL4-3 or with NL4-3/Denv, and with either supernatants from the Neuro-2a FasL cell line (Neuro-2a FasL), which contain microvesicle-bound, unprocessed CD95L, 57 51,[53][54][55] Western blot analysis of the purified supernatants of living or dying (serum deprived) control HeLa cells, using a CD95L-specific antibody, showed the presence of a 39-40 kDa CD95L in the latter (as in the positive control Jurkat cell cytoplasmic lysates) and no detectable CD95L in the former (Figure 5c). To further investigate the potential role of CD95L, we incubated CD4 þ T cells with supernatants from the Neuro-2a FasL cell line, which contain microvesicle-bound, unprocessed CD95L released by these cells.…”
Section: Cd95l Released By Dying Cells Is One Of the Cellular Factorsmentioning
confidence: 99%
“…of three independent experiments cells. To study this point, we chose the Jurkat derived cell clone, Jhan-Tat, which undergoes apoptosis upon serum withdrawal more rapidly than K562-Tat cells (Li et al, 1995;Westendorp et al, 1995a). Thus, Jhan-Tat cells and the parental Jhan cell line were incubated with the cell-permeable caspase-3 inhibitor z-DEVDcmk, and half of the cells were cultured in medium containing 10% FCS, and the other half cultured under low serum conditions (0.1% FCS) for 6 h. Then, ROS generation and Dc m dissipation were detected as described above for K562 cells.…”
Section: Loss Of Mitochondrial Membrane Potential (Dc M ) and Reactivmentioning
confidence: 99%
“…The molecular mechanism of apoptosis in HIV-1 infection is largely unknown but several reports indicate that T cell apoptosis might be a ected by viral proteins such as HIV-Tat (Li et al, 1995;McCloskey et al, 1997;Patki and Lederman, 1996;Sastry et al, 1996;Westendorp et al, 1995a;Zauli et al, 1996), and gp120 (Banda et al, 1992;Herbein et al, 1998;Tuosto et al, 1995;Westendorp et al, 1995a). It has been shown that HIV-1-Tat upregulates the expression of CD95L in human peripheral T cells and accelerates CD95-mediated apoptosis (Westendorp et al, 1995a), and that this viral protein can downregulate not only the bcl-2 gene expression in a variety of hematopoietic cell types, but also increase the expression of the proapoptotic gene Bax (Sastry et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tat can modulate the expression of cytokines and cellular genes [6][7][8][9][10][11], and chemokine receptors [12][13][14][15], which are responsible for the transmission of macrophageand T-cell-tropic HIV-1 strains, respectively. In addition, the Tat protein also plays key roles in viral pathogenesis and in the pathogenesis of acquired immune deficiency syndrome (AIDS)-associated Kaposi's sarcoma [8,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%